0988 Electronic Sleep Disorder Screening in Employees of a Large Healthcare System: A Pilot study. (12th April 2019) - Somboon, Thapanee; Bruton, Monica; Wang, Lu; Bena, James; Foldvary-Schaefer, Nancy
Abstract: Introduction: Sleep disorders, highly prevalent in the general population, are associated with a host of adverse health outcomes, daytime impairment and healthcare costs. We performed a pilot study using a mobile application to explore interest in sleep disorder screening and estimate the prevalence of common sleep disorders in employees of a larger healthcare system. Methods: 30, 000 healthcare system employees (60% of all employees randomly selected) were invited to participate in an electronic sleep screening pilot over 12 months in 2015-2016 using intranet announcements and letters from the employee health plan. Participants completed the Epworth Sleepiness Scale (ESS), Insomnia Severity Index (ISI) and STOP instruments and provided habitual sleep duration and work hour/shift data. Results were summarized for the entire cohort and by work shift status. Comparison between work shifts was performed by Kruskal-Wallis test, Chi-square test and Fisher's exact test. Pairwise comparisons was performed by Bonferini correction. Results: A total of 2, 851 employees (9.5% of invitees) participated (86% first shift, 5% second shift and 9% third shift workers). Self-reported prior sleep diagnoses included sleep apnea (13%), insomnia (7%), restless legs syndrome (5%) and circadian rhythm disorders (1%). Habitual sleep duration was lower in third shift (6[5.0, 6.0]) than first (6[6.0, 7.0]) and second shift workers (6[5.0, 7.0]) (p<0.001). Elevated ESS (≥11) was observed in 871 (31%) participants. 779 (27%) had ISI ≥15 and 962 (37%) had STOP scores ≥2. Elevated ESS was more common in third shift (42%) than first (30%) and second shift (28%) workers (p<0.001). First shift employees were less likely to have moderate-to-severe insomnia symptoms (25%) than second (39%) and third shift (46%) workers (p<0.001). No difference in high risk OSA was observed (p=0.1). Conclusion: High-risk OSA, moderate-to-severe insomnia symptoms and daytime sleepiness are highly prevalent in healthcare employees. Significant insomnia and daytime sleepiness were more common in third shift than first and second shift workers. These findings support the need for further work exploring the impact of sleep disorder symptoms and the role of sleep education on employee health and work performance. Support (If Any)